2020
DOI: 10.1101/2020.05.08.20095067
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Mathematical Model Approach for Prevention and Intervention Measures of the COVID–19 Pandemic in Uganda

Abstract: The human-infecting corona virus disease caused by the novel severe acute respiratory syndrome corona virus 2 (SARS-CoV-2) was declared a global pandemic on March 11th, 2020. Current human deaths due to the infection have raised the threat globally with only 1 African country free of Virus (Lesotho) as of May 6th, 2020. Different countries have adopted different interventions at different stages of the outbreak, with social distancing being the first option while lock down the preferred option for flattening … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Uganda has imposed the most strict lockdown, while Tanzanian restrictions have been less severe than the other two countries. In Uganda, lockdown entailed closing the normal conducting of business, severely restricting lifestyle of people; leaving only essential aspects of the community functioning ( Mbabazi et al, 2020 ). Public transport was suspended, motor cyclists were prohibited from carrying passengers and only allowed to carry small items including delivering food to individual households.…”
Section: Government Measuresmentioning
confidence: 99%
“…Uganda has imposed the most strict lockdown, while Tanzanian restrictions have been less severe than the other two countries. In Uganda, lockdown entailed closing the normal conducting of business, severely restricting lifestyle of people; leaving only essential aspects of the community functioning ( Mbabazi et al, 2020 ). Public transport was suspended, motor cyclists were prohibited from carrying passengers and only allowed to carry small items including delivering food to individual households.…”
Section: Government Measuresmentioning
confidence: 99%
“…There are several theories and interventions that came up in a wake to fight the virus. These included mathematical or statistical models, lockdowns, clinical trials, treatment options and vaccination among others [6,7,8,2].…”
Section: Findings and Discussionmentioning
confidence: 99%
“…A model [8] focused on the rate of infection with time and it could ably predict and project the pandemic for some period ahead. Several other studies especially on the long-term symptoms of COVID-19 were identified [11].…”
Section: Mathematical Modelingmentioning
confidence: 99%
“…Implementing an AI-based system does not come cheap as many associated activities and requirements are costly or even hard to obtain especially in developing countries like Uganda. Authors of the reviewed papers highlighted the financial hardships faced in acquiring and annotating datasets [17,24], hardware and computing resources [24,43,49], and system maintenance and upgrading [29,42]. Modern AI-driven systems leverage deep learning neural networks that require very high computing hardware compared to traditional machine learning algorithms.…”
Section: Cost Of Ai Implementationmentioning
confidence: 99%